A Cognitive Stylistic: Irony and Sarcasm in The Lyrics of Lana Del Rey’S “Norman F***Ing Rockwell!” Using Schema Theory - Arifah, Dinillah; Sigalingging, Anggi Yolanda; Rangkuti, Rahmadsyah (Jurnal Penelitian Inovatif, 2025)
This study explore how figure of speech in Norman Fucking Rockwell! by Lana Del Rey is construct meaning through cognitive stylistic lens with focus on schema theory, approached by cognitive stylistics, specifically, the use of schema theory. Using qualitative textual analysis, this study investigates key lyrical expression that evoke disillusionment and critique idealized romantic narratives. It examines the use of irony, sarcasm, metaphor and repetition, interact with listener’s cognitive frameworks to decipher the implications of its message of normative schema of love and masculinity. Sarcastic lines like “Godd**n, man-child” and ironic contrasts such as “Why wait for the best when I could have you?” disrupt conventional expectations and prompt interpretive reevaluation. The findings show that these figures of speech are not merely rhetorical devices but central mechanisms in activating and subverting audience schemata, thereby deepening the emotional complexity and critical stance of the song. This study contributes to a clearer understanding of how cognitive stylistic features especially irony and sarcasm shape listener interpretation and reveal layered meaning in lyric based narratives.